Implementation of Anti-fraud Strategy at Bank Sulselbar in South and West Sulawesi Province - Mappisabbi, Muhammad Fadli; Hasniati, ‎; Ibrahim, Muhammad Akmal (KnE Social Sciences, 2025)
Fraud is an act of deviation, often occurring in financial services institutions. Every financial services institution is expected to implement an anti-fraud strategy by considering the characteristics of comprehensive fraud potential and implementing a fraud control system. This study uses a qualitative method to analyze the implementation of anti-fraud strategies at Bank Sulselbar in South and West Sulawesi Provinces. Primary data sources are obtained from in-depth interviews with various informants who play important roles in implementing anti-fraud strategies. Secondary data relates to statistical data related to fraud. The data analysis technique used is interactive analysis. The results of the study found that the anti-fraud strategy at Bank Sulselbar was carried out by issuing a Director’s Decree number: SK/068/DIR/K/XII/2024 concerning Standard Operating Procedures (SOP) for the Implementation of the Anti-Fraud Strategy of PT. Bank Sulselbar. Other prevention efforts are carried out by building anti-fraud awareness, carrying out verifications and surprise audits, and using fraud detection systems. In addition, the Know Your Customer and Know Your Employee policies have been implemented but have not been consistent. In detecting fraud, the whistleblowing system method is used, but its implementation has not been optimal. Investigations and reporting are carried out in accordance with applicable procedures. Sanctions are given by implementing zero tolerance for fraudulent acts. Evaluations are carried out periodically and continuously and various findings are followed up according to applicable mechanisms.